The importance of long-term relationship for the sustainability of Malaysian herbal industry - Hamid, Nurul Syahira; Mohd Nawi, Nolila; Man, Norsida; Mohamed, Zainal Abidin (Institut Penyelidikan Perhutanan Malaysia, 2015)
Herbal industry is one of the most promising industries in the future. The rapid development of the herbal industry in Malaysia is reflected by its trade. Herbal industry is one of the EPP in NKEA and government wants to improve the product quality and marketing efforts of the herbal industry. The government also targeted both upstream and downstream segments of the industry to help in developing the industry. Long-term relationship has been acknowledged as capable in increasing the competitiveness of an industry. It has been found that retailers or buyers with long-term relationships can achieve a competitive advantage by receiving merchandise in short supply, information on new and best-selling products and competitive activity, best allowable prices, and advertising and markdown allowances. Furthermore, buyers and sellers are interdependence in the industry thus, to increase the efficiency and probability to success, it is necessary to identify the factors that affecting the development of long-term relationship among supply chain players in the Malaysian herbal industry. Based on previous studies, there are a number of variables that can contribute to the maintenance of collaborative long-term relationship such as commitment, satisfaction, trust, power-dependence, communication, reputation and others. It has been identified that the relationship building efforts are theorized to enhance their membership’s commitment to the relationship as well as the membership’s relationship behaviors. Satisfaction has also been acknowledged as the buyer’s cognitive state of being adequately rewarded for the sacrifices undergone in facilitating the exchange which can help in sustaining the industry. Satisfaction also encourages greater loyalty and a long-term working relationship. Trust is also one of the important factors that can increase the sustainability of the industry. Trust is the willingness to rely upon an exchange partner in whom who has confidence and facing the risk together. Many benefits can be obtained by buyers and sellers through development of long term relationships. Through a long-term relationship, supply chain players in the Malaysian herbal industry are able to gain advantages that may be not realized under a traditional relationship.